2022
DOI: 10.26828/cannabis/2022.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Expectancies for Cannabis-Induced Emotional Breakthrough, Mystical Experiences and Changes in Dysfunctional Attitudes: Perceptions of the Potential for Cannabis-Assisted Psychotherapy for Depression

Abstract: Psychedelic-assisted psychotherapy has established antidepressant effects. Cannabis users appear to expect high doses administered in a session much like psychedelic-assisted psychotherapy to create comparable subjective effects. The current studies explored expectations of antidepressant effects of such cannabis-assisted sessions to replicate and extend previous work. Users not only expected a cannabis-assisted psychotherapy session to decrease depression, but also to alter some of the same mediators of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…As many of the studies cited in this review did not involve standardized doses, study participants could very well have been using cannabis at levels too low to generate a psychedelic experience. This supposition is supported by a recently published study of cannabis users' beliefs regarding cannabis-guided psychotherapy (Earleywine et al, 2022). Results illustrated an expectation that cannabis could produce psychedelic effects when administered at an unspecified "ideal dose."…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As many of the studies cited in this review did not involve standardized doses, study participants could very well have been using cannabis at levels too low to generate a psychedelic experience. This supposition is supported by a recently published study of cannabis users' beliefs regarding cannabis-guided psychotherapy (Earleywine et al, 2022). Results illustrated an expectation that cannabis could produce psychedelic effects when administered at an unspecified "ideal dose."…”
Section: Discussionmentioning
confidence: 59%
“…As many of the studies cited in this review did not involve standardized doses, study participants could very well have been using cannabis at levels too low to generate a psychedelic experience. This supposition is supported by a recently published study of cannabis users’ beliefs regarding cannabis-guided psychotherapy (Earleywine et al, 2022). Results illustrated an expectation that cannabis could produce psychedelic effects when administered at an unspecified “ideal dose.” Differences in the patterns of therapeutic use between cannabis and classic psychedelics—with classic psychedelics typically administered over the course of a few intensive therapy sessions and cannabis used more frequently and independent of therapy sessions—may also explain why cannabis has not been more frequently associated with psychedelic experiences (Johnstad, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…For instance, understanding whether CAP is preferentially suited for treating D-PTSD, assuming that all assisted forms of psychedelics are available. A recent cross-sectional study, investigating expectations for CAP, showed comparable beliefs to psilocybin-assisted therapy among two samples of cannabis users ( 58 ). Participants believed that CAP, when administered at an ideal dose, could elicit mystical and emotional experiences, as well as alter dysfunctional attitudes.…”
Section: Discussionmentioning
confidence: 98%
“…Moving beyond good or bad moods, here we wonder how cannabis changes people's discrete emotions (Fredrickson, 2009)-for example, awe, gratitude, love, etc. By appreciating the emotional profile of frequent cannabis intoxication, we might better understand what drives use and possibly identity novel applications for cannabis, say in therapeutic contexts (Earleywine et al, 2022).…”
Section: Emotions Motivation and Self-regulationmentioning
confidence: 99%